Methods Of Achieving High Effectiveness In Foreign Language Teaching - Bolibekova, Mavjuda Mardievna; Juraeva, Iroda Akhmedovna; Kakharova, Nafisa Ikramovna; Nazarova, Dilshodakhon Ochildinovna (The journal of contemporary issues in business and government, 2021)
This article discusses methods for achieving high efficiency in foreign language teaching. And also article provides solid advice for learning foreign languages. The methodology of teaching by age category is also analyzed, an individual approach is recommended, the psychological preparedness of the teacher, the need for verbal and visual aids when teaching a foreign language. Mastering a foreign language is a certain stage in the formation of a personality from a pedagogical point of view. The article also examines national traditions, views of the educators of the East and West on the problems of learning foreign languages.